2017
DOI: 10.3923/ijp.2017.593.602
|View full text |Cite
|
Sign up to set email alerts
|

Oral Intake of Aged Garlic Extract (AGE) Ameliorates Oxidative Stress and Other Streptozotocin-induced Diabetic Complications in Rats

Abstract: The anti‐diabetic and antioxidant effects of oral administration of aged garlic extract (AGE) were studied in diabetic rats. Diabetes was induced by IP injection of streptozotocin (60mg/kg, STZ), and a fasting blood sugar >300 mg/dl indicated diabetes. AGE (Wakunaga‐Kyolic, USA) was administered orally at a dose of 600 mg/kg daily for 8 weeks. Diabetic rats were divided into 2 groups, diabetic control and AGE‐treated diabetic. A normal, saline‐treated, control group was also included. STZ‐induced diabetic rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Additionally, aged garlic extract significantly attenuated the elevation of serum triglyceride, total cholesterol, and lowered lipid peroxidation in liver and kidney tissues [96]. A similar type of result was also reported in the study performed by Thomson et al [97] and Seo et al [30], where aged garlic extract reduced the oxidative stress markers, improved insulin sensitivity, dyslipidemia, and other complications of diabetes in male Sprague-Dawley rats and C57BL/KsJ-db/db mice, respectively. Another study examined the anti-diabetic effects of BG powder in male Wister rats and found that BG powder lowered blood glucose, prevented glycogen in the liver, and improved lipid metabolism by increasing the activity of glutamic oxaloacetic transaminase, glutamic pyruvic transaminase, and γ-GTP [98].…”
Section: Effects Of Black Garlic On Metabolic Disorders 611 Black Garlic and Diabetes Mellitussupporting
confidence: 66%
“…Additionally, aged garlic extract significantly attenuated the elevation of serum triglyceride, total cholesterol, and lowered lipid peroxidation in liver and kidney tissues [96]. A similar type of result was also reported in the study performed by Thomson et al [97] and Seo et al [30], where aged garlic extract reduced the oxidative stress markers, improved insulin sensitivity, dyslipidemia, and other complications of diabetes in male Sprague-Dawley rats and C57BL/KsJ-db/db mice, respectively. Another study examined the anti-diabetic effects of BG powder in male Wister rats and found that BG powder lowered blood glucose, prevented glycogen in the liver, and improved lipid metabolism by increasing the activity of glutamic oxaloacetic transaminase, glutamic pyruvic transaminase, and γ-GTP [98].…”
Section: Effects Of Black Garlic On Metabolic Disorders 611 Black Garlic and Diabetes Mellitussupporting
confidence: 66%